Peningkatan Keterampilan Menulis Teks Deskripsi Menggunakan Pendekatan Kontekstual Dengan Media Objek Pengamatan Langsung Siswa Kelas VII SMP Negeri 3 Abab - Amra, Hoiril; Rukiyah, Siti; M, Missriani (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Language is a tool of human communication for both oral and written. In Indonesian learning, there are four skills that are expected to continue to improve in students. These four skills include reading, writing, speaking, and listening. Writing skills are one of the skills that have a high level of difficulty compared to other aspects of skills. One of the writing materials learned by grade VII junior high school students is writing description texts. Teachers need to consider suitable models, methods, media, and approaches in teaching writing this description text. In this study, the author used a contextual approach with direct observation object media when teaching material to write description texts. The results of this study show an increase in the skills of writing description texts for grade VII students of SMP Negeri 3 Abab for the 2023/2024 school year. This is evidenced by obtaining student grades, namely in the first cycle students achieved completeness as many as 12 students out of 26 students or 45%. In cycle II students achieved completeness of 21 students out of 26 students or 81%, an increase of 36%. From the results of this study, it can be concluded that a contextual approach with direct observation object media is more suitable to be applied in writing description texts.